Analisis Sistem Aplikasi Pembayaran Uang Kuliah - Irfan Sudahri Damanik (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Application of the application program to the manual system into a computer system will change the pattern of technology of a system. Thus the existing human resources must be able and have the potential to control and maintain the existing system because aspects of brainware is essential for the running of a computer system that is maximal and reliable. There are many obstacles encountered in a manual system such as inaccurate and inefficient data information because the data has not been neatly arranged so that the transition of manual system into computer system gives ease in handling data in large scale with efficient and effective time. Financial transactions can be done if the status of a student is active, it is difficult to do with manual system that is not directly connected with the education division that regulates student activeness. Then how the student data in the academic section with financial division data to obtain accurate data about the status of students. Is every transaction listed on the receipt that the student takes in accordance with what is stored in the financial division.